Factors causing ordinary level female students to drop out of school and the effects these could have in Zaka district - Dudzai, Ruzvidzo (Midlands State University, 2020)
The purpose of this study is to find out the factors causing female students to drop out of school and the effects this could have in Zaka District. The researcher was motivated to carry out the study because uneducated women lead to underdevelopment of a country, poor healthy standards, as well as promoting antisocial behaviour. A sample of two schools, two school heads, eight teachers, ten students enrolled as well as five drop outs were used. The qualitative research design was used which enabled the researcher to get all the necessary information needed. Instruments used were document analysis and interview guide. Those instruments were used because they allow the researcher to get actual information required. Data were generated and presented in the form of themes and tables. Poverty, death and separation of parents are some of the major reasons why students drop out of school. Students should be involved in Guidance and counselling clubs and fund raising activities so that they are equipped with life survival skills. The Basic Education Assistance Module should increase the funds given to vulnerable students so that they get all the necessary resources for education to take place.